1971
DOI: 10.1128/jb.105.1.369-375.1971
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Thermal Stability of Intact Bacillus subtilis Flagella

Abstract: Flagella were prepared and purified in a relatively intact form from bacterial lysates. Immunochemical tests showed that over 95% of the protein in the final preparation consisted of flagellar antigen. These flagella are more stable to thermal denaturation than flagella filaments obtained by shearing. Their thermal properties more closely resemble those of flagella in the native state on bacteria. The presence of the hook structure is responsible for this extra stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

1972
1972
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…At the proximal end of the hook, a distal rod was often attached, as was described previously for E. coli and S. typhimurium (Fig. 1, A and B, arrows;Dimmitt and Simon, 1971;Okino et al, 1989).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…At the proximal end of the hook, a distal rod was often attached, as was described previously for E. coli and S. typhimurium (Fig. 1, A and B, arrows;Dimmitt and Simon, 1971;Okino et al, 1989).…”
Section: Resultsmentioning
confidence: 61%
“…For both genera, the flagellar filament and hook have been extensively analysed, because they are external to the cell and, therefore, easy to purify. Intact flagella that contain the basal structures at the proximal end of the hook were isolated from both Escherichia coli and Bacillus subtilis at about the same time (Dimmitt and Simon, 1971;DePamphilis and Adler, 1971a,b). Electron-microscopic observations revealed characteristic features of the basal-body structures from both genera; four (two inner and two outer) rings and a rod for E. coli, and two (inner) rings and a rod for B. subtilis.…”
Section: Introductionmentioning
confidence: 99%
“…It is now possible to isolate from bacteria "intact" flagella, i.e. flagella with the basal structure still attached (76)(77)(78). There is the helical filament, a hook, and a rod.…”
Section: F the Functioning Of Flagella To Produce Bacterial Motionmentioning
confidence: 99%
“…There is the helical filament, a hook, and a rod. In the case of E. coli, four rings are mounted on the rod (76), while flagella from grampositive bacteria have only the two inner rings (76,78). For E. coli it has been established that the outer ring is attached to the outer membrane and the inner ring to the cytoplasmic membrane (Fig.…”
Section: F the Functioning Of Flagella To Produce Bacterial Motionmentioning
confidence: 99%
“…In order to understand these regulatory processes, it is necessary that we have a clear picture of the structure of the organelle. Biochemical and electron microscope (3) studies have shown that the flagella are composed of three morphologically distinct sections: a) the flagellar filament (4) accounts for over 95% of the mass of the organelle and it is made u p of identical protein subunits (flagellin); b) the filament ends in a short "hook" region which is also made up of subunitshowever, the subunits in the hook (5)-differ from those in the filament; c) the hook (6,7) is attached to a caplike structure, which in gram positive organisms (7) consists of two discs that are mounted on a thin tubular shaft. The discs are bound t o the cell membrane and the cell wall.…”
Section: Introductionmentioning
confidence: 99%